2019
DOI: 10.1177/1352458519872644
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities are prevalent and detrimental for employment outcomes in people of working age with multiple sclerosis

Abstract: Background: More work is needed to understand the burden of comorbidities in people with multiple sclerosis (MS). Objective: To assess prevalence of 30 comorbidities and impacts of comorbidities on employment outcomes in a working-aged MS cohort. Methods: Participants were from the Australian MS Longitudinal Study ( n = 929). Information on specific comorbidity was obtained (whether or not each was present, doctor-diagnosed, limited their activities and being treated). Results: Comorbidities most frequently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…26 Another large cohort study in Sweden found that persons having MS with depression had a higher risk of reaching major disability milestones, including EDSS scores of 3.0, 4.0, and 6.0. 34 Mood and anxiety disorders, as well as migraine, another prevalent comorbidity among our immigrant cohort, have been shown to be major causes of limited work activities in the Australian MS Longitudinal Study of 929 persons with MS. 35 Depression, along with physical comorbidity, was correlated with decreased health-related quality of life in a Canadian cross-sectional study of 949 persons with MS. 36 Overall, depression and anxiety are known to be underdiagnosed and undertreated in individuals with MS. 37,38 Brief, self-reported psychometric scales can assist with screening for these conditions. 38 Pharmacotherapy, cognitive behavioral therapy, mindfulness-based therapy, and exercise programs may all offer therapeutic benefit although there is no gold standard approach to treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…26 Another large cohort study in Sweden found that persons having MS with depression had a higher risk of reaching major disability milestones, including EDSS scores of 3.0, 4.0, and 6.0. 34 Mood and anxiety disorders, as well as migraine, another prevalent comorbidity among our immigrant cohort, have been shown to be major causes of limited work activities in the Australian MS Longitudinal Study of 929 persons with MS. 35 Depression, along with physical comorbidity, was correlated with decreased health-related quality of life in a Canadian cross-sectional study of 949 persons with MS. 36 Overall, depression and anxiety are known to be underdiagnosed and undertreated in individuals with MS. 37,38 Brief, self-reported psychometric scales can assist with screening for these conditions. 38 Pharmacotherapy, cognitive behavioral therapy, mindfulness-based therapy, and exercise programs may all offer therapeutic benefit although there is no gold standard approach to treatment.…”
Section: Discussionmentioning
confidence: 98%
“… 26 Another large cohort study in Sweden found that persons having MS with depression had a higher risk of reaching major disability milestones, including EDSS scores of 3.0, 4.0, and 6.0. 34 Mood and anxiety disorders, as well as migraine, another prevalent comorbidity among our immigrant cohort, have been shown to be major causes of limited work activities in the Australian MS Longitudinal Study of 929 persons with MS. 35 Depression, along with physical comorbidity, was correlated with decreased health-related quality of life in a Canadian cross-sectional study of 949 persons with MS. 36 …”
Section: Discussionmentioning
confidence: 98%
“…Chen et al 18 report on MS days lost that there is a mean total absenteeism of 0.6 days per 4 weeks or 7.8 days per person annually. Symptom severity in people with MS most strongly explains workforce participation and productivity 19 . They assessed prevalence and impact of 30 comorbidities on participation and productivity in work, and the economic burden and productivity costs of comorbidities.…”
Section: Why Is This Important To People's Health?mentioning
confidence: 99%
“…Symptom severity in people with MS most strongly explains workforce participation and productivity. 19 They assessed prevalence and impact of 30 comorbidities on participation and productivity in work, and the economic burden and productivity costs of comorbidities. Depression (45%) followed by anxiety (42%), allergies (38%), migraine (30%), and high blood pressure (25%) were the five most prevalent comorbidities.…”
Section: Multiple Sclerosis: Costs To Individuals Families and The Economymentioning
confidence: 99%
“…Symptom severity in people with MS most strongly explains workforce participation and productivity. 15 They assessed prevalence and impact of 30 comorbidities on participation and productivity in work, and the economic burden and productivity costs of comorbidities. Depression (45%) followed by anxiety (42%), allergies (38%), migraine (30%) and high blood pressure (25%) were the five most prevalent comorbidities.…”
Section: Multiple Sclerosis (Ms): Costs To Individuals Families and mentioning
confidence: 99%